THE EFFECT OF PROLONGED SMARTPHONE USE ON CHILDREN’S COGNITIVE FUNCTIONING - Umedova M. E.; Egamberdiyev D. (The Conference Hub, 2025)
Over the past decade, smartphones and other personal screen devices have become an integral part of children’s daily lives. Screen-based activities have turned into the primary medium for play, education, and communication among children; as a result, their daily screen time (ST) has increased substantially.